Tractor operated fertilizer applicator in the application of wheat crop root zone - PATEL, ANURAG; S C, Moses (Indian Farming, 2022)
Cautiousness for quality food and environment sustainability has led to the genesis of Good Agricultural Practices (GAP) which have now acquired global acknowledgement for facilitating internal and external trade in agricultural produce and products. Most of the developed economies have already developed their own GAP standards. In such global scenario, India cannot remain aloof, therefore, Quality Council of India (QCI) has developed guidelines for Indian Good Agricultural practices (BasicGAP and INDGAP). This scheme comprises of control points and their compliances for all the crop production components to seek certification from the accredited bodies. Adherence to GAP would help Indian farmers in producing safe and quality food for domestic market and boost their confidence for competing in international arena. In fact, this is the roadmap for enhancing their income in coming decade. Keywords: Agribusiness, Good Agricultural Practices (GAP), Quality Council of India (QCI)